2015
DOI: 10.1021/acs.jpca.5b11991
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra and Theoretical Calculations of cis- and trans-3-Fluoro-N-methylaniline in the Neutral (S0) and Cationic (D0) Ground States

Abstract: The mass-analyzed threshold ionization spectra of jet-cooled cis- and trans-3-fluoro-N-methylaniline (3FNMA) were recorded by ionizing via the vibrationless 0(0) and various vibrational levels of the S1 state. The adiabatic ionization energies of cis- and trans-3FNMA are determined to be 61,742 ± 5 and 61,602 ± 5 cm(-1), respectively. In the 0-1800 cm(-1) region, most of the observed vibrations in the D0 state result from the in-plane ring deformation and substituent-sensitive modes. For the high-frequency vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…As demonstrated in our previous study, [28] ionization can trigger the conformational switching of some aromatic com-pounds. The ionization/oxidation effect on the conformational preferences of o-methoxyheteroarenes is investigated, as tabulated in Table 1.…”
Section: Conformational Preferences Of O-heteroaromatic Ethers: Effecsupporting
confidence: 61%
“…As demonstrated in our previous study, [28] ionization can trigger the conformational switching of some aromatic com-pounds. The ionization/oxidation effect on the conformational preferences of o-methoxyheteroarenes is investigated, as tabulated in Table 1.…”
Section: Conformational Preferences Of O-heteroaromatic Ethers: Effecsupporting
confidence: 61%
“…3, cis 2MOP is more stable than trans 2MOP in the S 0 , S 1 and D 0 states, suggesting the existence of the syn preference in all the three electronic states. It is interesting to know whether the syn conformational preference found for many compounds in the S 0 state 12,16,18,25 will remain in the S 1 and D 0 states. The question seems still open and some results of qualitative estimations are listed in Table 2.…”
Section: C-r2pi Spectra Of 2mop and 2nmpmentioning
confidence: 99%
“…Weersink et al 17 examined the excitation spectrum of N,N-dimethylaniline to analyze geometrical shifts and proposed that the structural change along torsional motions of the two CH 3 rotors upon excitation is responsible for the weak origin band. Recently, we found that the ionization could alter the relative stability of 3-fluoro-N-methylaniline 18 conformers related to the rotation of the methylamino group, giving a stable cis in the S 0 state but a stable trans in the D 0 state. While spectroscopic and theoretical investigations 19 on conformers related to the CH 3 rotation demonstrated that for diethyl ether (DEE), the neutral state has a stable conformer quite different from that of the cationic state, but for diethyl sulfide (DES), the two states have similar conformers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the trans- 2-fluorothioanisole molecule (2FTA) was found to be planar in the S 0 and D 0 states, while it is slightly distorted in the S 1 state; stable planar cis- and trans- rotamers were observed in each of the S 0 , S 1 , and D 0 states for 3-chlorothioanisole (3ClTA) . The stable structures for most anisole derivatives have been found to be planar, while stable nonplanar structures were determined for C 6 H 5 SCF 3 and N-methylaniline (NMA) derivatives. …”
Section: Introductionmentioning
confidence: 97%